Converting candlenut shell waste into graphene for electrode applications - Siburian, Rikson; Tarigan, Kerista; Manik, Yosia Gopas Oetama; Hutagalung, Fajar; Alias, Yatimah; Chan, Yong Ching; Chang, Boon Peng; Siow, Jonathan; Ong, Amanda Jiamin; Huang, Jingfeng; Paiman, Suriati; Goh, Boon Tong; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Graphene was synthesized through a two-step pyrolysis method using waste candlenut (Aleurites moluccanus) shells as the precursor. Cerium (Ce)/graphene composites were prepared via an impregnation technique. The resulting graphene and Ce/graphene were characterized using various analytical methods, including Scanning Electron Microscopy with Energy-Dispersive Spectroscopy (SEM-EDS), X-ray Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Transmission Electron Microscopy (TEM), Thermo Gravimetric Analysis (TGA), Fourier Transform Infrared (FTIR) spectroscopy, Cyclic Voltammetry (CV), and Linear Sweep Voltammetry (LSV). The bio-carbon produced predominantly exhibited a graphene structure with flat carbon morphology and an interlayer distance of 0.33 nm. This structural information is supported by XRD data, which shows a broad and weak peak at 2θ = 26° corresponding to the C (002) plane, indicative of graphene presence. FTIR, XPS, and Raman spectroscopy further confirmed the presence of graphene through the detection of Csp2 aromatic bonds and the characteristic D, G, and 2D peaks. Notably, the performance of cerium can be enhanced by the incorporation of graphene, attributed to the large surface area and chemical interactions between Ce and graphene. Consequently, candlenut-derived graphene shows potential as a supportive material for modifying the properties of cerium, due to the current value of Ce/Graphene increase with presence of graphene, thereby opening avenues for various advanced applications, such as sustainable and high-performance energy storage systems.